The dual role of CD70 in B‐cell lymphomagenesis. Issue 12 (5th December 2022) - Nie, Man; Ren, Weicheng; Ye, Xiaofei; Berglund, Mattias; Wang, Xianhuo; Fjordén, Karin; Du, Likun; Giannoula, Yvonne; Lei, Dexin; Su, Wenjia; Li, Wei; Liu, Dongbing; et al.
Abstract: Background: CD70 is a costimulatory molecule that is transiently expressed on a small set of activated lymphocytes and is involved in T‐cell‐mediated immunity. However, the role of CD70 in B‐cell malignancies remains controversial. Methods: We investigated the clinical relevance of CD70 genetic alterations and its protein expression in two diffuse large B‐cell lymphoma (DLBCL) cohorts with different ethnic backgrounds. We also performed transcriptomic analysis to explore the role of CD70 alterations in tumour microenvironment. We further tested the blockade of CD70 in combination with PD‐L1 inhibitor in a murine lymphoma model. Results: We showed that CD70 genetic aberrations occurred more frequently in the Chinese DLBCL cohort (56/233, 24.0%) than in the Swedish cohort (9/84, 10.8%), especially in those with concomitant hepatitis B virus (HBV) infection. The CD70 genetic changes in DLBCL resulted in a reduction/loss of protein expression and/or CD27 binding, which might impair T cell priming and were independently associated with poor overall survival. Paradoxically, we observed that over‐expression of CD70 protein was also associated with a poor treatment response, as well as an advanced disease stage and EBV infection. More exhausted CD8 + T cells were furthermore identified in CD70 high‐expression DLBCLs. Finally, in a murine lymphoma model, we demonstrated that blocking the CD70/CD27 and/or PD1/PD‐L1 interactions could reduce CD70 + lymphoma growth in vivo, by directly impairing the tumour cell proliferation and rescuing the exhausted T cells. Conclusions: Our findings suggest that CD70 can play a role in either tumour suppression or oncogenesis in DLBCL, likely via distinct immune evasion mechanisms, that is, impairing T cell priming or inducing T cell exhaustion. Characterisation of specific dysfunction of CD70 in DLBCL may thus provide opportunities for the development of novel targeted immuno‐therapeutic strategies. Abstract : 1 CD70 mutations/deletions result in reduction/loss of CD70 expression and are enriched in patients with concomitant HBV infection. 2 Overexpression of CD70 is associated with EBV infection and a more immunosuppressive tumour microenvironment. 3 CD70 plays both tumour suppressive and oncogenic roles in diffuse large B‐cell lymphoma.